Service providers’ perspectives on facilitators and recommendations for improving HIV care in Manitoba, Canada - Maier, Katharina; Haworth-Brockman, Margaret; Villacis-Alvarez, Enrique; Mackenzie, Lauren J.; Ireland, Laurie; Kasper, Ken; Keynan, Yoav; Rueda, Zulma Vanessa (Frontiers in Public Health, 2025)
BackgroundWe aimed to identify facilitators and recommendations for improving HIV care in Manitoba, Canada from service providers’ perspectives.MethodsThis study is a component of a participatory action research study examining the interrelatedness of houselessness, substance use and other factors on HIV care. We conducted in-depth, semi-structured interviews with 27 HIV service providers in Manitoba (Canada). Interviews were transcribed, coded, and analyzed using a thematic approach within a socio-ecological framework.ResultsWe identified 11 supertheme facilitators and 15 supertheme recommendations at the intrapersonal, interpersonal, socio-cultural, institutional and structural levels. For the facilitators, subthemes include non-judgmental care (intrapersonal), focus on building relationships and trust (interpersonal), collaboration with other providers (socio-cultural), safe non-stigmatizing environments (institutional), and effective policies (structural). Provider recommendations highlight the need for structural changes, with subthemes focused on policy changes, adaptations to HIV care delivery model, harm reduction strategies, and addressing gaps in social services and mental health care.ConclusionService providers’ behaviours and attitudes as well as organizational processes play a significant role in PLHIV engagement and retention in HIV care. Institutional and structural changes, including flexible and mobile HIV care as well as integrated HIV and harm reduction care, are critical for increasing care uptake and retention.